Application of lacrimal endoscopy in the diagnosis and treatment of primary canaliculitis: Practical technique and graphic presentation. Issue 33 (August 2019) - Zheng, Qingqing; Shen, Ting; Luo, Hongbo; Hong, Chaoyang; He, JinJing; Gong, Jingwen; Jiang, Jin
Abstract : Abstract: To investigate the efficacy of lacrimal endoscopy in the diagnosis and treatment of primary canaliculitis. This is a retrospective, interventional study. Fifteen patients diagnosed as primary canaliculitis were investigated, who underwent surgery with lacrimal endoscopy from January 2015 to December 2017 at Zhejiang Provincial People's Hospital. Patients were subsequently followed post-operatively for at least 6 months. Pre- and post-operative main measurement included ocular surface symptoms, signs of canaliculitis, intraoperative images, treatment response and complications. Twelve patients (12 eyes) were enrolled. Endoscopy was successful in revealing the residual concretion and pathological change of lacrimal duct. With its unique direct vision and micro drill, all concretions got removed and lacrimal ducts got patent. On postoperative month 6, all of the patients got cured with no signs of redness, swelling of the punctum and eyelid, epiphora with discharge and pain. None serious complications such as false canalicular passage were observed. Lacrimal endoscopy is indispensable in diagnosis, treatment and follows up of primary canaliculitis. With less iatrogenic injury, higher resolution rate and direct observation of canalicular mucosa, lacrimal endoscopy should be widely applied in the management of lacrimal diseases.